High-strength red copper material and preparation method thereof

By controlling the content of specific elements in copper materials and optimizing the processing technology, the problems of copper materials in bending processing and surface quality are solved, and high strength, low warpage and excellent surface performance are achieved, which are suitable for a variety of application fields.

CN119194155APending Publication Date: 2024-12-27CHINALCO DAYE COPPER PLATE & STRIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411304619.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing copper materials are prone to bending cracking, plating and warping problems during bending processing, and the finished strips have high internal stress, which affects the yield and performance.

Method used

By controlling the content range of elements such as Sn, Fe, P, O, Zn, Te, As, and combining optimized processing technology, such as hot rolling, cold rolling, annealing and finishing rolling, ensure the composition uniformity and structure of the material. Structure, reduce internal stress, improve bending performance and surface quality.

Benefits of technology

It realizes high bending processability, low warpage and excellent surface performance of high-strength copper materials, and meets the application needs of automobile water tanks, heat sinks, motor rectifiers and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194155A_ABST
    Figure CN119194155A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of copper alloy, in particular to a high-strength red copper material and a preparation method thereof.The high-strength red copper material comprises, by weight, 0.1%-0.15% of Sn, 0.003%-0.005% of Fe, 0.005%-0.009% of P, 0.005%-0.01% of O, 0.008%-0.018% of at least two elements of Zn, Te and As and the balance copper and inevitable impurities, the preparation method of the high-strength red copper material comprises the steps of burdening, smelting and heat preservation, semi-continuous casting, heating in a heating furnace, hot rolling, surface milling, rough rolling and annealing, finished product rolling and annealing, finished product shearing, packaging and warehousing, and the high-strength red copper strip is obtained. And the application requirements in the fields of automobile water tanks, cooling fins, motor commutators, relays and the like are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper alloys, and in particular to a high-strength copper material and a preparation method thereof. Background Art

[0002] Low-tin copper strip is a copper alloy with low tin content, such as C14415. It has a higher softening temperature than pure copper and has good creep, stress relaxation and fatigue resistance. It has good corrosion resistance in natural atmosphere, industrial atmosphere and coastal atmosphere, and has stronger resistance to erosion and pitting in water or neutral salt water. This material is widely used in automotive water tanks, heat sinks, motor commutators, relays and other fields. The material needs not only high strength and hardness, but also excellent bending processability.

[0003] However, when the products prepared by the existing technology are bent into parts, they often bend and crack, which seriously affects the yield rate of the product group. At the same time, the strip often leaks plating during the subsequent electroplating process, which seriously affects the performance of the product; in addition, the finished strip often warps. Based on this, there is an urgent need for a copper material with excellent comprehensive performance, which has excellent surface properties, bending processing performance and lower internal stress while ensuring high strength. Summary of the invention

[0004] In view of this, the present invention proposes a high-strength copper material and a preparation method thereof, aiming to solve the problem in the prior art that the strength, hardness, bending performance and processing performance of the copper material cannot be coordinated and controlled.

[0005] To solve the above problems, the present invention provides a high-strength copper alloy material, which, calculated by weight percentage as 100%, comprises: 0.1-0.15% Sn, 0.003-0.005% Fe, 0.005-0.009% P, 0.005-0.01% O and 0.008-0.018% of at least two elements of Zn, Te and As, and the balance is copper and unavoidable impurities.

[0006] In some embodiments, the weight percentage of Zn is 0.05-0.08%; and / or, the weight percentage of Te is 0.005-0.01%; and / or, the weight percentage of As is 0.005-0.008%.

[0007] Another aspect of the present invention provides a method for preparing the above-mentioned high-strength copper material, comprising the following steps:

[0008] Step 1, preparing raw materials according to the composition of the high-strength copper material, the raw materials comprising: electrolytic copper, CuSn master alloy, CuFe master alloy, CuP master alloy, and a first raw material, the first raw material being selected from at least two of pure Zn, CuTe master alloy and CuAs master alloy, sequentially adding the prepared raw materials into a smelting furnace for smelting and heat preservation, converting the raw materials into a heat preservation furnace after the composition is qualified, and draining the raw materials into a crystallizer through a casting pipe for semi-continuous casting to obtain a copper ingot;

[0009] Step 2: heating and keeping the copper ingot warm in a heating furnace in an oxidizing atmosphere, then hot rolling it on a hot rolling mill, and then double-sided milling it on a milling machine to obtain a hot-rolled billet;

[0010] Step 3, rough rolling the hot-rolled billet on a four-roll rough rolling mill, cleaning and degreasing it, and then annealing it to obtain an annealed rough-rolled billet;

[0011] Step 4: rolling the annealed rough-rolled billet into finished product on a finishing mill, degreasing and annealing the billet to obtain a finished annealed billet;

[0012] Step 5: Cut, package and store the finished annealed blank to obtain a finished strip product.

[0013] In some embodiments, in step 1, the converter temperature is 1200-1220°C, and the casting temperature is 1180-1200°C.

[0014] In some embodiments, in step 2, the heating temperature of the heating furnace is 900-940°C, the holding time is 4-6h, the air-fuel ratio of the oxidizing atmosphere is 1.08-1.15, the hot rolling passes are 7 passes, the total hot rolling deformation is 75-80%, the deformation of the 5th pass is 35-38%, and the deformation of the 6th pass is 28-32%.

[0015] In some embodiments, in step three, the rough rolling mill uses 7 cold rolling passes, the total cold rolling deformation is 75-80%, the deformation of the 5th pass is 28-32%, the deformation of the 6th pass is 26-32%, the annealing temperature is 420-470°C, and the holding time is 8-14h.

[0016] In some embodiments, in step 4, the finished product is rolled 3 times, the total deformation of the first and second passes is 55-60%, and the roller roughness is 0.3 μm; the deformation of the third pass is 40-44%, and the roller roughness is 0.15 μm.

[0017] In some embodiments, the annealing temperature in step 4 is 480-520° C., and the tape speed is 40-50 m / min.

[0018] In some embodiments, in step five, the shear tension is 25-35 Kgf, the tension accuracy is 3-5%, and the pressing force is 0.15-0.25 Kgf.

[0019] In some embodiments, the copper material has a tensile strength of 440-480 MPa, a Vickers hardness of 130-150 HV, an elongation ≥ 6%, a conductivity ≥ 85% IACS, a GW 90 degree bending R / t ≤ 0.5, a BW 90 degree bending R / t ≤ 0.5, a surface roughness ≤ 0.15 μm, and a warpage < 40 mm / 1000 m.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention controls the contents of Sn, Fe, P, O, Zn, Te, As and other elements in the high-strength copper material within a specific range. Through the synergistic effect of these alloy elements, not only the balance of strength, conductivity and bending is ensured; at the same time, through the optimization of the processing technology, the bending and surface quality of the strip are further improved, so that the high-strength copper has higher bending processability and lower warpage on the basis of high strength. It can meet the application needs in automobile water tanks, heat sinks, motor commutators, relays, etc. Compared with the prior art, the method has the characteristics of high strength, excellent surface quality, low internal stress and excellent bending processability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 This is a warpage diagram of the high-strength copper prepared in Example 1 of the present invention;

[0024] Figure 2 This is a warpage diagram of the high-strength copper prepared in Comparative Example 1 of the present invention;

[0025] Figure 3 This is a surface appearance diagram of the high-strength copper prepared in Example 1 of the present invention;

[0026] Figure 4 This is a surface appearance diagram of the high-strength copper prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.

[0029] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.

[0030] When an amount, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range. In the present specification and claims, range definitions can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.

[0031] Existing copper materials are prone to bending and cracking problems when bending parts. Many reasons may cause this problem, including unreasonable deformation process parameters during cold rolling and / or hot rolling, which may lead to inconsistent grain sizes, resulting in stress concentration points, and ultimately cracking during bending. During the cold rolling process, when the material hardening degree is too high, the ductility will be reduced, making it unable to flow and easy to crack during bending. At the same time, the poor distribution uniformity of alloy elements will also form hard and brittle phases or impurities of intermetallic compounds, which become cracking sources during the bending process. The problem of missing plating in the strip during the electroplating process may be caused by the presence of oxides or pollutants on the surface of the strip, which hinders the deposition of the coating, or the uneven surface roughness or excessive roughness, which causes the plating solution to be unable to evenly cover the entire surface and thus miss plating. Secondly, excessive internal stress will also cause microcracks or defects on the surface, making it impossible for the plating solution to be evenly deposited on the surface of the strip. The warping problem of the strip is mainly due to the presence of residual stress inside, or unreasonable parameter conditions in the cooling process.

[0032] In order to solve the above-mentioned shortcomings, the present application aims to solve the problem that the comprehensive performance of the copper material cannot meet the production needs by controlling the material composition, optimizing the element selection and ratio, and secondly optimizing the processing technology. The high-strength copper material is calculated as 100% by weight, and its element composition includes: 0.1-0.15% Sn, 0.003-0.005% Fe, 0.005-0.009% P, 0.005-0.01% O and 0.008-0.018% of at least two elements of Zn, Te, and As, and the balance is copper and unavoidable impurities.

[0033] The inventor aims to achieve better comprehensive performance of copper materials by optimizing the composition of the alloy. The innovation of this copper material lies in the ingenious integration of the composition of metal elements in the alloy, including copper (Cu), tin (Sn), iron (Fe), phosphorus (P), oxygen (O) and at least two elements selected from zinc (Zn), tellurium (Te), and arsenic (As). Through the precise design of the elements and the content of the elements, the comprehensive performance of copper is improved synchronously, which not only retains high strength, but also has excellent surface properties, bending properties and processing properties and low internal stress. Specifically:

[0034] Tin (Sn) forms a solid solution in the copper matrix, increasing the strength and hardness of the material. Since the atomic radius of Sn is different from that of Cu, it causes lattice distortion and hinders dislocation movement. At the same time, Sn improves the corrosion resistance of alloy materials, especially in acidic and neutral media, by forming a protective oxide film to reduce corrosion. Moreover, the appropriate addition of Sn can improve the strength of the material while maintaining good conductivity.

[0035] Iron (Fe) precipitates in the copper matrix to form tiny second phase particles, such as Cu-Fe phase. These particles are evenly distributed in the copper matrix, playing a role of precipitation strengthening, hindering dislocation movement, and trace amounts of Fe refine the grains, improving the mechanical properties and processing properties of the material. Refined grains also help improve the toughness and strength of the material.

[0036] Phosphorus (P) exists in the copper matrix in the form of solid solution, increasing the hardness and strength of the material. The atomic radius of P is different from that of Cu, and it can also play a role in lattice distortion and hinder dislocation movement. Moreover, the segregation of P at the grain boundary helps to stabilize the grain boundary structure, reduce the tendency of hot cracks, and improve the casting performance. The P content is controlled within a specific range to ensure that the influence of P on the conductivity of high-strength copper is minimized, so that it can meet the use requirements.

[0037] Oxygen (O) combines with impurity elements in copper alloys, such as Fe and P, to form tiny oxide particles. These particles are distributed in the copper matrix, which helps to inhibit grain growth and refine grains. Trace amounts of oxygen are controlled within a specific range to help remove excess impurities that may exist during the smelting process, maintain the purity of the material, and reduce the H content in the melt. At the same time, the content of oxygen cannot be too high. Excessive oxygen content affects the bending performance of high-strength copper. Therefore, the O content is controlled within a specific range.

[0038] Zinc (Zn) helps to improve the material's antioxidant capacity, forming a zinc oxide protective film on the surface of copper to reduce oxidation and corrosion. Zn can also refine the grains and enhance the ductility and toughness of the material.

[0039] Tellurium (Te) can form tiny second phases in the copper matrix, such as Cu-Te phases. These particles help strengthen the copper matrix and hinder dislocation movement. In addition, trace amounts of Te help refine the grain structure and improve the mechanical properties of the material. Too high a content will affect the processing properties of the material, while too low a content will not have the corresponding effect.

[0040] Arsenic (As) can improve the corrosion resistance of materials, especially in acidic and alkaline media, by forming a protective oxide film on the surface to reduce corrosion. In addition, arsenic can also enhance the strength of the copper matrix by forming fine compound particles.

[0041] Based on the formula of each metal element provided above, the strength and hardness of the material are improved by solid solution strengthening, precipitation strengthening and grain refinement among the metal elements. At the same time, the elements cooperate with each other to further comprehensively enhance the strength, corrosion resistance, conductivity, bending processability, internal stress control, etc. of the copper alloy material.

[0042] More preferably, in the copper alloy material provided by the present invention, the weight percentage of Zn is 0.05-0.08%; and / or the weight percentage of Te is 0.005-0.01%; and / or the weight percentage of As is 0.005-0.008%.

[0043] Another aspect of the present invention further provides a method for preparing the copper alloy material based on the above improved formula, comprising the following steps:

[0044] Step S1, preparing raw materials according to the composition of the high-strength copper material, the raw materials comprising: electrolytic copper, CuSn master alloy, CuFe master alloy, CuP master alloy, and a first raw material, the first raw material being selected from at least two of pure Zn, CuTe master alloy and CuAs master alloy, sequentially adding the prepared raw materials into a smelting furnace for smelting and heat preservation, transferring the raw materials to a heat preservation furnace after the components are qualified, and draining the raw materials into a crystallizer through a casting pipe for semi-continuous casting to obtain a copper ingot;

[0045] Step S2, heating and keeping the copper ingot warm in a heating furnace, the heating atmosphere is an oxidizing atmosphere, then hot rolling on a hot rolling mill, and then double-sided milling on a milling machine to obtain a hot-rolled billet;

[0046] Step S3, rough rolling the hot-rolled billet on a four-roll rough rolling mill, cleaning and degreasing it, and then annealing it to obtain an annealed rough-rolled billet;

[0047] Step S4, rolling the annealed rough-rolled billet into finished product on a finishing mill, degreasing and oiling the billet, and then annealing the billet to obtain a finished annealed billet;

[0048] Step S5: cutting, packaging and storing the finished annealed blank to obtain a finished strip product.

[0049] In the preparation method provided by the present invention, the copper ingot is heated and kept warm in a heating furnace, which promotes the composition and organization inside the ingot to be more uniform, and improves the performance of the final product; helps to eliminate the casting stress inside the ingot and reduce defects in the processing process; the micro-oxidizing atmosphere avoids the problem of hydrogen embrittlement, and the grains of the ingot can be broken and refined by hot rolling on a hot rolling mill, thereby improving the mechanical properties of the material, such as strength and toughness; and eliminates the component segregation and microstructural inhomogeneity in the ingot, making the material organization more uniform, thereby improving the overall performance. The hot-rolled billet is subjected to multiple cold rolling treatments, which can introduce a large number of dislocations, enhance the strength and hardness of the material, annealing eliminates the hardening effect caused by cold rolling, and restores the ductility and machinability of the material. Finally, the finishing rolling treatment improves the surface properties of the material and reduces surface defects, which can not only control the final thickness and uniformity, but also improve the strength and hardness and ensure the ductility of the material.

[0050] In the above embodiment, in step 1, the converter temperature is 1200-1220° C. and the casting temperature is 1180-1200° C. Casting at this temperature can ensure that all alloy elements are fully dissolved and evenly distributed, and are drained to the crystallization through the pouring pipe for casting. Maintaining the above appropriate casting temperature range is conducive to forming a uniform ingot.

[0051] Furthermore, in step 2, the heating temperature of the heating furnace is 900-940°C, the holding time is 4-6h, the air-fuel ratio of the oxidizing atmosphere is 1.08-1.15, the hot rolling passes are 7 passes, the total hot rolling deformation is 75-80%, the deformation of the 5th pass is 35-38%, and the deformation of the 6th pass is 28-32%.

[0052] Seven hot rolling passes are carried out on the hot rolling mill. By controlling the hot rolling deformation of the 5th and 6th passes, the organization and performance of the material can be significantly affected. By controlling the hot rolling deformation of these two passes, the casting defects can be significantly eliminated, the organizational structure can be optimized, and the mechanical properties of the final copper alloy material can be improved. By controlling the appropriate air-fuel ratio, surface oxidation can be reduced, the quality of the material surface can be improved, the milling amount can be reduced, and the probability of defects such as bubbles and peeling in the material can be reduced.

[0053] In the scheme of the present application, in step three, the rough rolling mill adopts 7 cold rolling passes, the total cold rolling deformation is 75-80%, the deformation of the 5th pass is 28-32%, the deformation of the 6th pass is 26-32%, the annealing temperature is 420-470°C, and the holding time is 8-14h.

[0054] By optimizing the deformation amount in the last pass of rough rolling, the grain refinement and recrystallization process can be controlled, the coarsening of grains can be reduced, and uniform and fine grains can be formed, thereby improving the strength and toughness of the material. This refinement process reduces the density of dislocations and forms a fine grain structure, which helps to improve the tensile strength and hardness of the material. At the same time, a large deformation amount in the last pass helps to eliminate the residual stress generated in the previous pass. The internal stress is released and redistributed in this process, which effectively reduces the internal stress level of the strip and reduces the risk of warping or deformation in subsequent processing. Moreover, this optimized rolling deformation treatment helps the strain hardening process so that the material can obtain the required mechanical properties. The larger deformation in the fifth pass increases the hardening degree of the material and improves the strength. The slightly smaller deformation in the sixth pass balances the strain hardening effect and maintains the appropriate ductility and toughness of the material. Secondly, the control of deformation can reduce surface defects and improve the flatness and smoothness of the strip. The larger deformation in the fifth pass may help introduce surface unevenness or defects in the previous pass of the sheeting material, making the material surface smoother and flatter, providing a good foundation for subsequent processing.

[0055] In the scheme of the present application, in step 4, the finished product is rolled 3 times, the total deformation of the first and second passes is 55-60%, and the roller roughness is 0.3μm; the deformation of the third pass is 40-44%, and the roller roughness is 0.15μm.

[0056] By controlling the deformation amount and the roughness of the roll in different passes of finishing rolling, the hardness and strength of the material can be improved, the residual stress introduced in rough rolling and annealing can be reduced, and the internal stress distribution can be optimized. Among them, the first two passes can achieve the final precise thickness control of the strip through appropriate deformation, ensure the dimensional consistency of the final product, reduce surface defects and roughness, and improve surface finish. The use of 0.3μm rolls in the first two passes can ensure that there is enough friction between the strip and the rolls to achieve uniform thickness deformation. At the same time, the larger roughness helps to homogenize the surface of the material, reduce surface irregularities, and provide a better surface state for subsequent processing. The third use of a 0.15μm roll can reduce the surface roughness and obtain a smooth final product surface, ensuring that the final surface of the strip has lower roughness and fewer defects. The lower roll roughness reduces the surface defects introduced during the processing, improves the uniformity and flatness of the strip surface, and optimizes the appearance quality of the product.

[0057] In the solution of the present application, the annealing temperature in step 4 is 480-520°C, and the tape speed is 40-50m / min.

[0058] In the scheme of the present application, the annealing temperature is 480-520°C to eliminate the work hardening introduced during the cold rolling process, reduce internal stress, optimize the material microstructure, and improve the surface finish. At the same time, the use of a suitable belt speed is intended to control the annealing time, control the residence time of the material in the annealing furnace, ensure that the annealing time is moderate, achieve uniform annealing, and avoid the phenomenon of uneven annealing due to too fast or too slow. Reasonable belt speed can also help to obtain the best mechanical properties and surface quality, and ensure the strength, hardness and ductility of the material.

[0059] In the solution of the present application, in step five, the shear tension is 25-35 Kgf, the tension accuracy is 3-5%, and the pressing force is 0.15-0.25 Kgf.

[0060] By controlling the shearing tension, tension accuracy, and clamping force, the accuracy and consistency of the strip during the shearing process are ensured, and a neat and smooth shearing edge is obtained, reducing burrs and irregular edges. In addition, appropriate tension and clamping force effectively reduce the deformation and surface damage of the strip during the shearing process, and improve the final product quality of the strip.

[0061] The copper material of the present application has a tensile strength of 440-480MPa, a Vickers hardness of 130-150HV, an elongation of ≥6%, a conductivity of ≥85%IACS, a GW 90-degree bending R / t≤0.5, a BW 90-degree bending R / t≤0.5, a surface roughness of ≤0.15μm, and a warpage of <40mm / 1000m. It can be applied to technical fields such as automotive water tanks, heat sinks, motor commutators, and relays.

[0062] Example 1

[0063] A method for preparing high-strength copper material:

[0064] The composition of the copper material is shown in Table 1 and Table 2.

[0065] The preparation process is: component design and batching → melting → alloying → semi-continuous casting → heating and insulation → hot rolling → rough rolling → annealing → cold rolling → annealing → finishing rolling → annealing → shearing and packaging.

[0066] Step S1, preparing raw materials according to the composition of the high-strength copper material, the raw materials comprising: electrolytic copper, CuSn master alloy, CuFe master alloy, CuP master alloy, and a first raw material, the first raw material being pure Zn and CuAs master alloy, sequentially adding the prepared raw materials into a smelting furnace for smelting and heat preservation, and transferring the raw materials to a heat preservation furnace after the components are qualified, the converter is transferred to a heat preservation furnace, the converter temperature is 1200° C., and the raw materials are drained into a crystallizer through a casting pipe for semi-continuous casting, the casting temperature is 1180° C., and a copper ingot is obtained;

[0067] Step S2, heating and keeping the copper ingot in a heating furnace, the heating temperature of the heating furnace is 940°C, the holding time is 4h, the heating atmosphere is an oxidizing atmosphere, the air-fuel ratio of the oxidizing atmosphere is 1.13, and then hot rolling is carried out on a hot rolling mill, the hot rolling passes are 7 passes, the deformation amounts of the 7 passes are respectively: 10%, 12%, 14%, 15%, 35%, 28%, 7.8%, and the total deformation amount is 75%, and then double-sided milling is carried out on a milling machine to obtain a hot-rolled billet;

[0068] Step S3, rough rolling the hot-rolled billet on a four-roll rough rolling mill, the rough rolling mill adopts 7 cold rolling passes, the total rolling deformation is 75%, and the deformations of the 7 passes are: 5%, 6%, 8%, 10%, 31%, 30%, 30.7%, respectively. After cleaning and degreasing, annealing is performed in a bell furnace, the bell furnace annealing temperature is 455°C, and the holding time is 12h, to obtain an annealed rough rolled billet;

[0069] Step S4, rolling the annealed rough-rolled billet into finished product on a finishing mill, rolling for a total of 3 passes, the deformation amount of the first pass is 27%, the deformation amount of the second pass is 30%, the roughness of the rolls in the first and second passes is 0.3 μm, the deformation amount of the third pass is 42%, the roughness of the rolls in the third pass is 0.15 μm, degreasing and oiling are performed, and then annealing is performed in an air cushion furnace, the annealing temperature of the air cushion furnace is 490° C., and the belt speed is 46 m / min, to obtain a finished annealed billet;

[0070] Step S5, shearing the finished annealed blank on a shearing machine, with a shearing tension of 25 Kgf, a tension accuracy of 4%, a clamping force of 0.15 Kgf, and packaging and storage to obtain a finished strip product.

[0071] Example 2

[0072] A method for preparing high-strength copper material:

[0073] The composition of the copper material is shown in Table 1 and Table 2.

[0074] The preparation process is: component design and batching → melting → alloying → semi-continuous casting → heating and insulation → hot rolling → rough rolling → annealing → cold rolling → annealing → finishing rolling → annealing → shearing and packaging.

[0075] Step S1, preparing raw materials according to the composition of the high-strength copper material, the raw materials comprising: electrolytic copper, CuSn master alloy, CuFe master alloy, CuP master alloy, and a first raw material, the first raw material being CuTe master alloy and CuAs master alloy, sequentially adding the prepared raw materials into a smelting furnace for smelting and heat preservation, and transferring the raw materials to a heat preservation furnace after the components are qualified, the converter is transferred to a heat preservation furnace, the converter temperature is 1210° C., and the raw materials are drained into a crystallizer through a casting pipe for semi-continuous casting, the casting temperature is 1195° C., and a copper ingot is obtained;

[0076] Step S2, heating and keeping the copper ingot in a heating furnace, the heating temperature of the heating furnace is 920°C, the holding time is 5h, the heating atmosphere is an oxidizing atmosphere, the air-fuel ratio of the oxidizing atmosphere is 1.15, and then hot rolling is carried out on a hot rolling mill, the hot rolling passes are 7 passes, the deformation amounts of the 7 passes are respectively: 14.3%, 14.3%, 14.3%, 14.4%, 37%, 29%, 20.3%, and the total deformation amount is 76%, and then double-sided milling is carried out on a milling machine to obtain a hot-rolled billet;

[0077] Step S3, rough rolling the hot-rolled billet on a four-roll rough rolling mill, the rough rolling mill adopts 7 cold rolling passes, the total rolling deformation is 76%, and the deformations of the 7 passes are: 14.2%, 14.2%, 14.2%, 14.2%, 32%, 28%, 10.6%, respectively. After cleaning and degreasing, annealing is carried out in a bell furnace, the annealing temperature of the bell furnace is 430° C., and the holding time is 10 hours to obtain an annealed rough rolled billet;

[0078] Step S4, rolling the annealed rough-rolled billet into finished product on a finishing mill, rolling for a total of 3 passes, the deformation amount of the first pass is 30%, the deformation amount of the second pass is 30%, the roughness of the rolls in the first and second passes is 0.3 μm, the deformation amount of the third pass is 40%, the roughness of the rolls in the third pass is 0.15 μm, degreasing and oiling are performed, and then annealing is performed in an air cushion furnace, the annealing temperature of the air cushion furnace is 490° C., and the belt speed is 50 m / min, to obtain a finished annealed billet;

[0079] Step S5, shearing the finished annealed blank on a shearing machine, with a shearing tension of 29 Kgf, a tension accuracy of 4%, a clamping force of 0.18 Kgf, and packaging and storage to obtain a finished strip product.

[0080] Example 3

[0081] A method for preparing high-strength copper material:

[0082] The composition of the copper material is shown in Table 1 and Table 2.

[0083] The preparation process is: component design and batching → melting → alloying → semi-continuous casting → heating and insulation → hot rolling → rough rolling → annealing → cold rolling → annealing → finishing rolling → annealing → shearing and packaging.

[0084] Step S1, preparing raw materials according to the composition of the high-strength copper material, the raw materials comprising: electrolytic copper, CuSn master alloy, CuFe master alloy, CuP master alloy, and a first raw material, the first raw material being pure Zn, CuTe master alloy and CuAs master alloy, sequentially adding the prepared raw materials into a smelting furnace for smelting and heat preservation, and transferring the raw materials to a heat preservation furnace after the components are qualified, the converter is transferred to a heat preservation furnace, the converter temperature is 1220° C., and the raw materials are drained into a crystallizer through a casting pipe for semi-continuous casting, the casting temperature is 1200° C., and a copper ingot is obtained;

[0085] Step S2, heating and keeping the copper ingot in a heating furnace, the heating temperature of the heating furnace is 900° C., the holding time is 6 hours, the heating atmosphere is an oxidizing atmosphere, the air-fuel ratio of the oxidizing atmosphere is 1.08, and then hot rolling is carried out on a hot rolling mill, the hot rolling passes are 7 passes, the deformation amounts of the 7 passes are respectively: 30%, 30%, 30%, 30%, 38%, 32%, 9%, and the total deformation amount is 80%, and then double-sided milling is carried out on a milling machine to obtain a hot-rolled billet;

[0086] Step S3, rough rolling the hot-rolled billet on a four-roll rough rolling mill, the rough rolling mill adopts 7 cold rolling passes, the total rolling deformation is 80%, and the deformations of the 7 passes are: 16.8%, 18.8%, 21.3%, 24.4%, 30%, 26%, 5.5%, respectively. After cleaning and degreasing, annealing is performed in a bell furnace, the annealing temperature of the bell furnace is 420° C., and the holding time is 14 hours to obtain an annealed rough rolled billet;

[0087] Step S4, rolling the annealed rough-rolled billet into finished product on a finishing mill, rolling for a total of 3 passes, the deformation amount of the first pass is 25%, the deformation amount of the second pass is 30%, the roughness of the rolls in the first and second passes is 0.3 μm, the deformation amount of the third pass is 44%, the roughness of the rolls in the third pass is 0.15 μm, degreasing and oiling are performed, and then annealing is performed in an air cushion furnace, the annealing temperature of the air cushion furnace is 500° C., and the belt speed is 43 m / min, to obtain a finished annealed billet;

[0088] Step S5, shearing the finished annealed blank on a shearing machine, with a shearing tension of 32 Kgf, a tension accuracy of 3%, a clamping force of 0.25 Kgf, and packaging and storage to obtain a finished strip product.

[0089] Example 4

[0090] A method for preparing high-strength copper material:

[0091] The composition of the copper material is shown in Table 1 and Table 2.

[0092] The preparation process is: component design and batching → melting → alloying → semi-continuous casting → heating and insulation → hot rolling → rough rolling → annealing → cold rolling → annealing → finishing rolling → annealing → shearing and packaging.

[0093] Step S1, preparing raw materials according to the composition of the high-strength copper material, the raw materials comprising: electrolytic copper, CuSn master alloy, CuFe master alloy, CuP master alloy, and a first raw material, the first raw material being pure Zn and CuTe master alloy, sequentially adding the prepared raw materials into a smelting furnace for smelting and heat preservation, and transferring the raw materials to a heat preservation furnace after the components are qualified, the converter is transferred to a heat preservation furnace, the converter temperature is 1215° C., and the raw materials are drained into a crystallizer through a casting pipe for semi-continuous casting, the casting temperature is 1185° C., and a copper ingot is obtained;

[0094] Step S2, heating and keeping the copper ingot in a heating furnace, the heating temperature of the heating furnace is 930° C., the holding time is 5 hours, the heating atmosphere is an oxidizing atmosphere, the air-fuel ratio of the oxidizing atmosphere is 1.1, and then hot rolling is carried out on a hot rolling mill, the hot rolling passes are 7 passes, the deformation amounts of the 7 passes are respectively: 9.1%, 11.4%, 14.2%, 17.7%, 36%, 31%, 6%, and the total deformation amount is 78%, and then double-sided milling is carried out on a milling machine to obtain a hot-rolled billet;

[0095] Step S3, rough rolling the hot-rolled billet on a four-roll rough rolling mill, the rough rolling mill adopts 7 cold rolling passes, the total rolling deformation is 78%, and the deformations of the 7 passes are: 10%, 11%, 12%, 13%, 28%, 29%, 9%, respectively. After cleaning and degreasing, annealing is performed in a bell furnace, the annealing temperature of the bell furnace is 470° C., and the holding time is 8 hours to obtain an annealed rough rolled billet;

[0096] Step S4, rolling the annealed rough-rolled billet into finished product on a finishing mill, rolling for a total of 3 passes, the deformation amount of the first pass is 30%, the deformation amount of the second pass is 28%, the roughness of the rolls in the first and second passes is 0.3 μm, the deformation amount of the third pass is 43%, the roughness of the rolls in the third pass is 0.15 μm, degreasing and oiling are performed, and then annealing is performed in an air cushion furnace, the annealing temperature of the air cushion furnace is 520° C., and the belt speed is 40 m / min, to obtain a finished annealed billet;

[0097] Step S5, shearing the finished annealed blank on a shearing machine, with a shearing tension of 35 Kgf, a tension accuracy of 5%, a clamping force of 0.22 Kgf, and packaging and storage to obtain a finished strip product.

[0098] Example 5

[0099] The other steps are the same as those in Example 1, except that, in step S2, the deformation amounts of the seven passes are 14%, 14%, 14%, 14%, 14%, 14%, and 13%, respectively.

[0100] Example 6

[0101] The other steps are the same as those in Example 1, except that, in step S3, the deformation amounts of the seven passes are 14%, 14%, 14%, 14%, 14%, 14%, and 13%, respectively.

[0102] Example 7

[0103] The other steps are the same as those in Example 1, except that in step S4, the deformation amounts of the three passes are 37.1% respectively.

[0104] Example 8

[0105] The other steps are the same as those in Example 1, except that the roughness of the rollers during the three rolling operations is 0.3 μm.

[0106] Example 9

[0107] The other steps are the same as those in Example 1, except that the roughness of the rollers during the three rolling operations is 0.15 μm.

[0108] Example 10

[0109] The other steps are the same as those in Example 1, except that, in step S2, the deformation amounts of the 7 passes are 14%, 14%, 14%, 14%, 14%, 14%, and 13%, respectively; in step S3, the deformation amounts of the 7 passes are 14%, 14%, 14%, 14%, 14%, 14%, and 13%, respectively; in step S4, the deformation amounts of the 3 passes are 37.1%, respectively.

[0110] Comparative Example 1

[0111] The other steps are the same as those in Example 1, except that the raw materials include electrolytic copper, CuSn master alloy, CuFe master alloy, CuP master alloy, and a first raw material, wherein the first raw material is pure Zn and CuAs master alloy in different proportions, and the composition is shown in Table 1 and Table 2.

[0112] Comparative Example 2

[0113] The other steps are the same as those in Example 1, except that the raw materials include electrolytic copper, CuSn master alloy, CuFe master alloy, CuP master alloy, and a first raw material. The first raw material is pure Zn, CuTe master alloy, and CuAs master alloy in different proportions. The compositions are shown in Tables 1 and 2.

[0114] Comparative Example 3

[0115] The other steps are the same as those in Example 1, except that the raw materials include electrolytic copper, CuSn master alloy, CuFe master alloy, CuP master alloy, but do not include the first raw material, whose composition is shown in Table 1.

[0116] Comparative Example 4

[0117] The other steps are the same as those in Example 1, except that the raw materials include electrolytic copper, CuSn master alloy, CuFe master alloy, CuP master alloy, and do not include the first raw material, and the composition thereof is shown in Table 1. Meanwhile, in step S2, the deformation amounts of the 7 passes are 14%, 14%, 14%, 14%, 14%, 14%, 13% respectively; in step S3, the deformation amounts of the 7 passes are 14%, 14%, 14%, 14%, 14%, 14%, 13% respectively; in step S4, the deformation amounts of the 3 passes are 37.1% respectively.

[0118] Table 1

[0119] Sn / % Fe / ppm P / ppm O / ppm X Example 1 0.1 0.003 0.009 0.005 0.008 Example 2 0.12 0.0035 0.008 0.007 0.015 Example 3 0.15 0.004 0.005 0.009 0.018 Example 4 0.14 0.005 0.006 0.01 0.014 Comparative Example 1 0.1 0.003 0.009 0.005 0.002 Comparative Example 2 0.1 0.003 0.009 0.005 0.035 Comparative Example 3 0.1 0.003 0.009 0.005 - Comparative Example 4 0.1 0.003 0.009 0.005 -

[0120] Table 2

[0121] Logo Zn Te As Example 1 0.005 0 0.003 Example 2 0 0.01 0.005 Example 3 0.005 0.005 0.008 Example 4 0.008 0.006 0 Comparative Example 1 0.001 0 0.001 Comparative Example 2 0.01 0.015 0.01

[0122] The performance of the copper materials prepared in the above examples and comparative examples was tested, and the data results shown in the following table were obtained:

[0123]

[0124]

[0125] It can be seen from the above data results that the improvement in the elemental composition of the copper material in the present application has a certain synergistic effect on the improvement of the comprehensive performance of the copper alloy, and can improve the surface performance, processing performance and lower internal stress of the copper alloy material while maintaining the good strength performance. Specifically, referring to the parameter results of Example 5 and Example 1, the deformation amount of each of the 7 passes of step S2 in Example 5 is not finely controlled. After using a single same deformation amount, the tensile strength and hardness of the plate are both reduced, while the surface flatness and warpage data are worse. This may be because during the hot rolling process, the deformation rolling control effect of different passes deteriorates, resulting in the internal defects generated in the casting stage cannot be effectively eliminated. It can be seen from the parameter results of Example 6 and Example 1 that when the rolling deformation control of 7 passes in step S3 is not performed according to the optimal data, the tensile strength and hardness of the plate will also be reduced, and the flatness and warpage are not as good as those of Example 1. Moreover, it can be seen from the warpage data that compared with the refined control in the hot rolling stage, Example 6 has a larger warpage when the hot rolling process is the same as that of Example 1. It is considered that the specific deformation amount of the last cold rolling pass can better release the residual stress inside the alloy material. It can be seen from the data comparison of Example 7 and Example 1 that the deformation control of the three finishing rolling passes in step S4 mainly has a certain impact on the mechanical properties of the alloy material. It is considered that the internal residual stress introduced from rough rolling and annealing should be eliminated through specific finishing rolling deformation control, and the finishing rolling step of Example 7 does not perform specific deformation amount control, so the residual stress elimination effect is not as good as that of Example 1.

[0126] In Example 8 and Example 9, the roughness of the rollers in different passes of the finishing rolling step was changed respectively. It can be clearly seen that the bending performance, surface roughness and warping of the obtained copper material were affected to varying degrees. Among them, when Example 9 used rollers with finer surfaces throughout the process, the bending effect was still not as good as that of Example 1. It is considered that the rolling of the first two passes of finishing rolling could not homogenize the surface structure, thereby reducing the bending performance of the final copper material.

[0127] Example 10 adopts conventional preparation technology, and its performance parameters in various aspects are far inferior to those in Example 1.

[0128] Similarly, from the comparison of the data of Comparative Examples 1 and 2 with the embodiment, it can be seen that even if the same raw materials and processes are used, when the component proportions are not within the preferred range of the present application, the performance parameters of various aspects of the final copper material are very different.

[0129] When Comparative Example 3 has the same composition ratio and preparation method as Example 1, but does not contain at least two elements of Zn, Te, and As, its various performance parameters are also difficult to reach the standards of Example 1. Therefore, the element ratio of the present application also contributes to the specific performance parameters of the red copper material of the present application.

[0130] When comparative example 4 adopts conventional element composition and conventional process, the performance parameters are not as good as those of embodiment 1, and compared with comparative example 3, it is also not as good as comparative example 3, indicating that when the preparation process of the present application is used for copper alloys with other element ratios, it will also produce certain performance optimization and has certain universality.

[0131] Moreover, the changes in elemental composition and the improvements in preparation technology can further enhance the comprehensive properties of copper alloy materials.

[0132] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-strength copper material, characterized in that: The invention comprises, by weight percentage, 0.1-0.15% Sn, 0.003-0.005% Fe, 0.005-0.009% P, 0.005-0.01% O and 0.008-0.018% at least two elements selected from Zn, Te and As, and the balance is copper and unavoidable impurities.

2. The high-strength copper material according to claim 1, characterized in that: The weight percentage of Zn is 0.05-0.08%; and / or, the weight percentage of Te is 0.005-0.01%; and / or, the weight percentage of As is 0.005-0.008%.

3. The method for preparing the high-strength copper material according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: Step 1, preparing raw materials according to the composition of the high-strength copper material, the raw materials comprising: electrolytic copper, CuSn master alloy, CuFe master alloy, CuP master alloy and a first raw material, the first raw material being selected from at least two of pure Zn, CuTe master alloy and CuAs master alloy, sequentially adding the prepared raw materials into a smelting furnace for smelting and heat preservation, converting the raw materials into a heat preservation furnace after the components are qualified, and draining the raw materials into a crystallizer through a casting pipe for semi-continuous casting to obtain a copper ingot; Step 2: heating and keeping the copper ingot warm in a heating furnace in an oxidizing atmosphere, then hot rolling it on a hot rolling mill, and then double-sided milling it on a milling machine to obtain a hot-rolled billet; Step 3, rough rolling the hot-rolled billet on a four-roll rough rolling mill, cleaning and degreasing it, and then annealing it to obtain an annealed rough-rolled billet; Step 4: rolling the annealed rough-rolled billet into finished product on a finishing mill, degreasing and annealing the billet to obtain a finished annealed billet; Step 5: Cut, package and store the finished annealed blank to obtain a finished strip product.

4. The method for preparing the high-strength copper material according to claim 3, characterized in that: In step 1, the converter temperature is 1200-1220°C and the casting temperature is 1180-1200°C.

5. The method for preparing the high-strength copper material according to claim 3, characterized in that: In step 2, the heating temperature of the heating furnace is 900-940°C, the holding time is 4-6h, the air-fuel ratio of the oxidizing atmosphere is 1.08-1.15, the hot rolling passes are 7 passes, the total hot rolling deformation is 75-80%, the deformation of the 5th pass is 35-38%, and the deformation of the 6th pass is 28-32%.

6. The method for preparing the high-strength copper material according to claim 3, characterized in that: In step three, the rough rolling mill adopts 7 cold rolling passes, the total cold rolling deformation is 75-80%, the deformation of the 5th pass is 28-32%, the deformation of the 6th pass is 26-32%, the annealing temperature is 420-470°C, and the holding time is 8-14h.

7. The method for preparing the high-strength copper material according to claim 3, characterized in that: In step 4, the finished product is rolled 3 times, the total deformation of the first and second passes is 55-60%, and the roll roughness is 0.3 μm; the deformation of the third pass is 40-44%, and the roll roughness is 0.15 μm.

8. The method for preparing the high-strength copper material according to claim 3, characterized in that: In step 4, the annealing temperature is 480-520° C. and the tape speed is 40-50 m / min.

9. The method for preparing the high-strength copper material according to claim 3, characterized in that: In step five, the shear tension is 25-35 Kgf, the tension accuracy is 3-5%, and the pressing force is 0.15-0.25 Kgf.

10. The high-strength copper material according to claim 1 or 2 or the high-strength copper material prepared by the method for preparing the high-strength copper material according to any one of claims 3 to 9, characterized in that: The copper material has a tensile strength of 440-480 MPa, a Vickers hardness of 130-150 HV, an elongation of ≥6%, a conductivity of ≥85% IACS, a GW 90 degree bending R / t≤0.5, a BW 90 degree bending R / t≤0.5, a surface roughness of ≤0.15 μm, and a warpage of <40 mm / 1000 m.